Influence of inorganic stabilizers on releasing volatile (As and Hg) metal ions from complex matrices of natural medicinal products in spectroscopic elemental analysis - Helal Uddin, A.B.M.; Khalid, Reem S.; Alaama, Mohammed; Abdualkader, Abdualrahman Mohammed; Abbas, S.A. (2016)
Arsenic (As) and mercury (Hg) are hazardous elements that occurs at trace amounts in various samples including natural medicinal products (NMPs). The consumption of the contaminated products leads to adverse health consequences. Regular monitoring of such contaminants in NMPs is essential. Atomic absorption spectroscopy has been widely used for determination of As and Hg at trace levels in various matrices. Spectroscopic analysis imposed sample digestion prior to instrumental analysis. This preliminary step has considerable impact on the quality of the analytical result especially for complex matrices like plants and herbs. Wet/acid digestion methods with suitable heating system are regularly used for this purpose. Microwave heating program is widely applied for digestion process of various matrices for the benefits of shorting the digesting time and minimizing the sample contamination. However, volatile analytes like As and Hg are susceptible to volatilization during the heating process. This study aims to evaluate the effect of NH4H2PO4, Pd (NO3)2, and Mg (NO3)2 addition prior to sample digestion on the recovery values of As and Hg in NMPs matrices by comparing the level accuracy of four digestion methods. The methods were M1, M2, M3 and M4 that represent microwave digestion without stabilizers addition, microwave digestion with addition of NH4H2PO4, microwave digestion with addition Pd (NO3)2, and Mg (NO3)2 and microwave digestion with addition Pd (NO3)2 respectively. The comparison was performed using three different real NMPs of herbal bases samples namely S1, S2 and S3 spiked with known concentration of a As and Hg standard solution prior to microwave acid digestion. Arsenic and mercury were detected with graphite furnace (GFAAS). Average recoveries of As for M1, M2, M3 and M4 were (86.87-89.17, 90.15-92.25, 97.9-100.7 and 103.7-108) respectively. Average recoveries of Hg for M1, M2, M3 and M4 were (87.4-89.3, 88.3-92.4, 95.0-95 107.6-104.7) respectively. The data was statically evaluated by one way analysis of variance (ANOVA) followed by Tukey HSD post hoc test for multiple comparison using Statistical Package for the Social Sciences (SPSS). Significant high recoveries (p<0.05) for M3 and M4 were observed compared to M1. In spite of the higher recoveries obtained from M2 compared to M1 no significant effect was observed between M1and M2. The addition of Pd (NO3)2, Mg (NO3)2 and Pd (NO3)2 during the digestion processes had significant effect on the recovery values of volatile elements thus, M3 and M4 are recommended procedures for the digestion of NMPs matrices for the determination of As and Hg.